PENGEMBANGAN KAWASAN AGROPOLITAN DI KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (Agropolitan Area Development in Modoinding District, Selatan Minahasa Regency) - Shania Bansaleng; Oktavianus Porajouw; Paulus A. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to describe the development of the Agropolitan Area of Mondoinding District in South Minahasa Regency. The study was carried out from July to September 2021. The data used came from secondary data were analyzed descriptively. The results showed that the development of Agropolitan Areas in Modoinding District experienced an increase in many sectors although there were still sectors that did not develop and some even experienced a decline. Land area and agricultural production increased by 99.7% and 99.8%, respectively. Agribusiness infrastructure and facilities, particularly banking, did not experience growth with only 2 banks from 2015 to 2019, while the cooperative sector experienced a decline of 40% and the market sector developed with the addition of 1 building. Public infrastructure and facilities, particularly the clean water sector, increased by 40%, while the lighting sector increased by 8.8%. The transportation sector had developed where all villages in Modoinding District already have asphalt roads. Communication had developed, where all village areas in Modoinding District have received telecommunication channels. The health sector did not develop, where health facilities in Modoinding District were still the same as before, while the education sector increased by 10.8 percent.